Cyberflashing : recognising harms, reforming laws / Clare McGlynn and Kelly Johnson. - McGlynn, Clare; Johnson, Kelly (Professor of criminology) (Bristol shorts policy and practice., 2021)
Cyberflashing has been on the rise since the Covid-19 pandemic. This book provides new analysis into the harms of cyberflashing. This timely and unique study considers recent laws in several countries and sets out proposals to criminalise cyberflashing in English law.